The management of persistent pulmonary hypertension of the newborn: A review - Lizel Georgi Lloyd; Johan Smith (South African Medical Association, 2016)
The first literary reference to persistent pulmonary hypertension (PH) of the newborn (PPHN) can be found in 1969 by Gersony et al., who described it as persistence of physiologic characteristics of the fetal circulation in the absence of disease. Defined as a failure of normal circulatory transition at birth, or more specifically as failure of the pulmonary vasculature to relax after birth, with continued shunting of non-oxygenated blood into the systemic circulation via fetal channels (ductus arteriosus and foramen ovale), it remains a challenging neonatal emergency to manage. Term and nearterm infants are most commonly affected, but PPHN can occur in premature infants.